2015
DOI: 10.1186/s40064-015-0912-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of six months of Yoga on inflammatory serum markers prognostic of recurrence risk in breast cancer survivors

Abstract: Yoga-based exercise has proven to be beneficial for practitioners, including cancer survivors. This study reports on the effect on inflammatory biological markers for 20 breast cancer survivors who participated in a six-month yoga-based (YE) exercise program. Results are compared to a comprehensive exercise (CE) program group and a comparison (C) exercise group who chose their own exercises.“Pre” and “post” assessments included measures of anthropometrics, cardiorespiratory capacity, and inflammatory markers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 74 publications
(89 reference statements)
0
56
0
Order By: Relevance
“…We identified 29 RCTs (see Table ): 13 RCTs were conducted during treatment (23 publications), 12 were conducted after treatment was completed (20 publications), and 4 included participants both during and after treatment. Only 4 studies included an active comparison group, such as supportive counseling, stretching, or a physical‐activity control group, and the others used a waitlist method or a usual‐care control group.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 29 RCTs (see Table ): 13 RCTs were conducted during treatment (23 publications), 12 were conducted after treatment was completed (20 publications), and 4 included participants both during and after treatment. Only 4 studies included an active comparison group, such as supportive counseling, stretching, or a physical‐activity control group, and the others used a waitlist method or a usual‐care control group.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed no weight loss, but decreased body fat and increased muscle mass for BCSs practicing yoga, indicating positive body composition changes, 60 but otherwise this has not been a topic of much research.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the influence of yoga on inflammation [50•, 57•, 60, 73, 74] and diurnal cortisol rhythms [49, 50•, 67]. For examples, Bower et al [50•] showed that breast cancer survivors who participated in 12 weeks of Iyengar yoga exhibited reduced activity of the pro-inflammatory transcription factor nuclear factor kappa B (NF-κB), increased activity of the anti-inflammatory glucocorticoid receptor, and reduced activity of the cAMP response element-binding (CREB) protein family transcription factors.…”
Section: Potential Biological Mechanismsmentioning
confidence: 99%
“…Kiecolt-Glaser et al [57•] also showed that 12 weeks of hatha yoga help reduced plasma IL-6 and IL-1β in breast cancer survivors and the reduction of these inflammation markers was associated with reduced CRF. However, Long Parma et al [73] found no changes in inflammatory markers among breast cancer survivors who participated in a 6-month yoga program. Banasik et al [49] showed that breast cancer survivors had lower morning and early evening salivary cortisol levels and improved emotional well-being and fatigue scores after 8 weeks of yoga practice compared to those in the standard care group.…”
Section: Potential Biological Mechanismsmentioning
confidence: 99%